Morphology, phase diagram, and properties of high‐density polyethylene/thermally treated waste polyethylene wax blends. Issue 10 (22nd October 2021) - Esmaeilzade, Romina; Sharif, Farhad; Rashedi, Reza; Dordi Nejad, Abdolkamal
Abstract: Waste polyethylene wax is thermally treated using a rotary evaporator to reduce unwanted components. Fourier transform infrared proves the absence of undesirable material. Wax is extruded with high‐density polyethylene (HDPE) at various loadings to study its morphology and final properties. Scanning electron microscopy and differential scanning calorimeter were employed to obtain the phase diagram showing the immiscibility of blends containing more than 20 wt% of wax. Due to the low melting temperature of the wax and its plasticating effect on HDPE, a decrease in melting temperature, enthalpy of fusion, and crystallinity with increasing wax content of the blend is observed. The phase diagram displays four possible phases depending on temperature and wax loading. Improved processability of HDPE/wax blends is demonstrated using complex viscosity curves. Han plots prove the miscibility of wax and HDPE in the melt state even at high concentrations of wax. HDPE/wax compounds have lower crystallinity, and wax particles, acting as weak spots, lower the elastic modulus, yield stress, and stress and strain at break as wax content increases. An increase in yield strain is observed due to the more effortless extension of HDPE chains at higher wax content. In 10 wt% of wax is accepted as the upper limit for wax incorporation into the HDPE matrix. Abstract : Waste polyethylene wax is thermally treated and blended with high‐density polyethylene (HDPE) at low and high concentrations. The miscibility of wax and HDPE is studied, and a phase diagram for the blends is obtained. Thermal, rheological, and mechanical properties of blends are also studied.